Measurement of the average very forward energy as a function of the track multiplicity at central pseudorapidities in proton-proton collisions at root s=13 TeV - (:unkn) unknown (SPRINGER, 2019)
The average total energy as well as its hadronic and electromagnetic components are measured with the CMS detector at pseudorapidities -6.6 < eta < -5.2 in proton-proton collisions at a centre-of-mass energy root s = 13 TeV. The results are presented as a function of the charged particle multiplicity in the region vertical bar eta vertical bar < 2. This measurement is sensitive to correlations induced by the underlying event structure over a very wide pseudorapidity region. The predictions of Monte Carlo event generators commonly used in collider experiments and ultra-high energy cosmic ray physics are compared to the data. All generators considered overestimate the fraction of energy going into hadrons.